Pengembangan repositori data pada lembaga riset dengan status Pusat Unggulan Ilmu Pengetahuan dan Teknologi - Cahyo Trianggoro; Tupan Tupan; Mohamad Djaenudin; Noorika Retno Widuri; Rochani Nani Rahayu (Jurnal Kajian Informasi dan Perpustakaan, 2021)
National regulations in science and technology mandate researchers, research institutions, and research funders to store and share research data. However, research institutions in Indonesia have not widely practiced research data management by utilizing institutional repositories. This study aimed to determine the development of repositories in research institutions under the Center of Excellence (PUI) supervision program from three aspects: policy, infrastructure, and organizational culture. This research used a quantitative approach through descriptive methods. Data was collected from the management of the research institute repository under the supervision program of the Center of Excellence (PUI), a program of the Ministry of Research and Technology/the National Research and Innovation Agency. The data were analyzed descriptively to see how the repository's development supported research activities. The study results indicated that most institutions had policies for managing institutional repositories on the policy side and needed to be reinforced by policies for managing research data. On the infrastructure aspect, most research institutions did not yet have a repository for research data management. While on aspects of cultural organization, most researchers realized that collaborative research activities could benefit from the institutional repository. This study concludes that research institutions can develop existing institutional repositories for research data management by reinforcing policies, improving the infrastructure function of institutional repositories, and building a culture of data management through campaigns and outreach.